Surgery vs. non-surgery for advanced cholangiocarcinoma post-conversion therapy with PD-1/PD-L1 inhibitors plus TKIs - Sun, Zengpeng; Wang, Yutao; Chen, Xu; Yang, Lishun; Li, Ou; Zhou, Jia; Tan, Zhiguo; Peng, Chuang (Frontiers in Immunology, 2026)
ObjectiveTo compare overall survival (OS) and progression-free survival (PFS) between surgical resection and non-surgical therapy in initially unresectable Cholangiocarcinoma (CCA) patients who achieved radiologic/MDT-confirmed resectability after PD-1/PD-L1 inhibitors plus TKIs.MethodsWe performed a retrospective analysis of 47 patients with initially unresectable CCA admitted between June 2020 and December 2024. Based on post-conversion treatment strategies, patients were divided into non-surgical resection (NR) and surgical resection groups (SR). We collected detailed baseline clinical data, treatment-related parameters, and long-term survival outcomes for all participants. Overall survival (OS) and progression-free survival (PFS) were compared between groups, with recurrence-free survival (RFS) analyzed in the SR. Cox regression was used to identify prognostic risk factors.ResultsThis study enrolled a total of 47 patients, including 23 in the SR and 24 in the NR. No significant differences were observed in baseline data between the two groups before conversion therapy. In the SR, the median overall survival (OS) was not reached, with 1-, 2-, and 3-year OS rates of 95.7%, 68.5%, and 68.5%, respectively. These survival outcomes were significantly superior to those observed in the NR, where the median OS was 28.5 months, and the 1-, 2-, and 3-year OS rates were 91.7%, 51.4%, and 17.6%, respectively (P = 0.026). Additionally, the SR exhibited a significantly longer median progression-free survival (PFS) of 19 months, with corresponding 1-, 2-, and 3-year PFS rates of 87.0%, 40.2%, and 25.2%. In contrast, the NR had a median PFS of 13.5 months and 1-, 2-, and 3-year PFS rates of 61.6%, 12.4%, and 12.4%, respectively (P = 0.025). Among patients in the SR, 21 cases (91.3%) achieved R0 resection, with no surgery-related mortality reported. The 1-, 2-, and 3-year recurrence-free survival (RFS) rates in this subgroup were 54.7%, 39.0%, and 29.3%, respectively.ConclusionFor patients with initially unresectable CCA, PD-1/PD-L1 inhibitors plus TKIs can successfully downstage the tumor. Conversion surgery is safe and feasible, and surgical treatment can improve patients’ OS and PFS.